(untitled) (Journal of Economic Research & Business Administration, 2015)
This article describes the history of beginning and development of economic relations branding in Kazakhstan. We have presented three main stages based on completed analysis. Perceptivity, the revealed negative aspects, the interfering high-grade formation of relations branding in the country, have allowed to build the present stage as arising.